ELMO3 predicts poor outcome in T1 laryngeal cancer. (13th March 2017) - Haymerle, G.; Kadletz, L.; Wiebringhaus, R.; Golabi, B.; Mildner, M.; Thurnher, D.; Heiduschka, G.
Abstract : Objectives: Despite the excellent overall survival of 92%‐97% in early glottic cancer, recurrence rates of 13%‐20% have not improved in the last decades. The engulfment and cell motility protein 3 (ELMO3) have been described as prognostic marker in patients with lung cancer. The aim of this study was to investigate the expression of ELMO3 in early laryngeal cancer patients treated with TLM and to evaluate its prognostic significance on clinical outcome. Design, setting and participant: Forty‐eight patients with glottic carcinoma (T1N0M0) that underwent primary treatment with TLM between 1994 and 2012 were analysed. ELMO3 expression of the tumour was assessed using immunohistochemistry and correlated with clinical data. Main outcome measure: Overall survival, disease‐specific survival (DSS) and disease‐free survival (DFS) rates Results: Positive ELMO3 expression was found in 23% of the patients and was correlated with poor DSS and DFS ( P <.05). Conclusion: This is the first study to show a prognostic effect of positive ELMO3 expression in early glottic carcinoma patients.